Cationic liposomes bearing Bet v 1 by coiled coil-formation are hypo-allergenic and induce strong immunogenicity in mice - Warmenhoven, Hans; Leboux, Romain; Bethanis, Athanasios; van Strien, Jolinde; Logiantara, Adrian; van Schijndel, Hans; Aglas, Lorenz; van Rijt, Leonie; Slütter, Bram; Kros, Alexander; Jiskoot, Wim; van Ree, Ronald (Frontiers in Allergy, 2023)
Although aluminum hydroxide (alum) is widely accepted and used as safe vaccine adjuvant, there is some concern about possible toxicity upon long-lasting repeated exposure during subcutaneous allergen immunotherapy (SCIT). Our objective was to evaluate allergen-bearing liposomes as possible alternative for alum-adsorption in SCIT. A self-assembling, coiled-coil forming peptide pair was used to anchor the major birch pollen allergen Bet v 1 to the surface of cationic liposomes. The resulting nanoparticulate liposomes were characterized with respect to their physicochemical, allergenic and immunological properties. Allergenicity was studied by ImmunoCAP inhibition and rat basophil leukemia (RBL) cell assays. Immunogenicity (immunoglobulin responses) and immune skewing (cytokine responses) were evaluated upon immunization of naïve mice, and compared to alum-adsorbed Bet v 1. Bet v 1-bearing cationic liposomes with a diameter of ∼200 nm showed a positive zeta potential. The coiled-coil conjugation of Bet v 1 to the surface of liposomes resulted in about a 15-fold lower allergenicity than soluble Bet v 1 as judged by RBL assays. Moreover, the nanoparticles induced Bet v 1-specific IgG1/IgG2a responses in mice that were several orders of magnitude higher than those induced by alum-adsorbed Bet v 1. This strong humoral response was accompanied by a relatively strong IL-10 induction upon PBMC stimulation with Bet v 1. In conclusion, their hypo-allergenic properties, combined with their capacity to induce a strong humoral immune response and a relatively strong IL-10 production, makes these allergen-covered cationic liposomes a promising alternative for aluminum salt-adsorption of allergen currently used in SCIT.